Educação no campo e luta de classes: um estudo sobre a produção acadêmica do GEPEC no período de 2010 a 2020 e sua atuação na formação inicial e continuada de professores - Santos, Patric Oberdan dos (2022)
Historically education aimed at the working class has not been a priority in Brazil. The expansion of the offer of Elementary Education only began to receive some attention from the national political class from the 1930s onwards, due to the need to train a workforce to boost the economic development project established by the government of Getúlio Vargas, guided by the binomial “urbanization-industrialization”. The universalization of Basic Education (Child Education, Elementary School and High School) is still a challenge to be effectively faced. Higher Education, in turn, has become an almost exclusive privilege of the ruling class, systematically denied to the working class, especially to peasants. In the perspective of undertaking the research, we defined as a first objective to verify the importance of scientific production and the contribution of the Group of Studies and Research in Education in the Field of the Federal University of São Carlos (GEPEC/UFSCar) for the development and improvement of public education, in especially that of the countryside; and as a specific objective to analyze the relationship between Marxian/Marxist theoretical foundations on education for rural populations and Historical-Critical Pedagogy (PHC). The methodology chosen for the development of the investigation had two fronts. The first consisted of a bibliographic approach, where we searched for the productions developed by GEPEC. The second methodology included a documental research, we sought to locate official documents that allowed us to understand the historical context of the creation of the Group. We conclude that GEPEC constitutes an important space for discussion about the realities that characterize life and work in the countryside through analyses, interpretations and reflections on education for rural populations, as well as for the knowledge and recognition of the importance of action and the role of social movements in the struggle and defense of agrarian reform and education.